Used Sources of Spiritual Growth for Spanish University Students - Muñoz García, Antonio (Religions, 2018)
Although some research has suggested means of promoting spiritual development in higher education, no systematic studies or literature reviews have been conducted to know what sources are most used for the spiritual growth of university students. This aspect was studied in a sample of 309 Spanish university students (Mean age = 21.40, range 18-25). The used sources were (in descending order) as follows: the practice of a virtuous behavior, cognitive-reflexive, nature-based, cultural, and religious sources. Women showed a higher use of cognitive-reflective and virtuous behavior-based sources. Age was related only and negatively to the use of religious sources. These results are consistent with previous studies indicating a greater religiosity in women and a lesser importance of religion in contemporary society and, particularly, in the life of young adults. However, taken as a whole, they indicate the importance of sociological and cultural aspects, in particular of the movement from traditional religiosity to religious indifference and dissatisfaction with institutional religion and/or toward spiritual movements linked to humanistic religions and spiritualities of life. It also points out the need to use a variety of strategies to foster the spiritual development of students.